Risk Disclosure and Risk Management of UK Real Estate Companies - Chen, Chen (2009)
This dissertation aims to research on the different approaches of risk disclosure and risk management currently adopted by the UK real estate companies. Literature review has been done on topics such as information disclosure, Corporate governance and risk disclosure in the UK, risk reporting debates, risk management and the Enterprise Risk Management. In the past years, we have witnessed many enterprise scandals due to careless risk management practice. The needs for more efficient corporate governance and higher risk management standard have been developed. After the global crisis, the issue of risk management is even more emphasised, and therefore the real estate industry has been facing increased pressure to disclosure more risk information in their annual reports. An increasing number of risk information disclosure and more sophisticated risk management practice suggests UK real estate companies adopt the market discipline to encourage more detailed risks in order to satisfy the stakeholders. A study of risk disclosure and risk management practices in the UK real estate industry is carried out using the sentence analysis methods. Five hypotheses are derived from the literature review and tested based on the content analysis of the annual reports and accounts of selected UK real estate companies. The results show that the real estate companies are putting an increase effort on risk disclosure and risk management practice. Larger real estate companies are disclosing more risks information and adopt more sophisticated risk management practice than smaller companies. Also, real estate companies are disclosing more “future risks” and “good risks” in their annual reports.